Virological and Serological Characterisation of SARS-CoV-2 Infections Diagnosed After mRNA BNT162b2 Vaccination Between December 2020 and March 2021 - Colavita, Francesca; Meschi, Silvia; Gruber, Cesare Ernesto Maria; Rueca, Martina; Vairo, Francesco; Matusali, Giulia; Lapa, Daniele; Giombini, Emanuela; De Carli, Gabriella; Spaziante, Martina; Messina, Francesco; Bonfiglio, Giulia; et al. (Frontiers in Medicine, 2022)
Background: Coronavirus disease 2019 (COVID-19) vaccines are proving to be very effective in preventing severe illness; however, although rare, post-vaccine infections have been reported. The present study focuses on virological and serological features of 94 infections occurred in Lazio Region (Central Italy) between December 27, 2020 and March 30, 2021, after one or two doses of mRNA BNT162b2 vaccine. Methods: We evaluated clinical features, virological (viral load; viral infectiousness; genomic characterization) and serological (anti-nucleoprotein Ig; anti-Spike RBD IgG; neutralizing antibodies, nAb) characteristics of 94 post-vaccine infections at the time of diagnosis. Nasopharyngeal swabs (NPS) and serum samples were collected in the framework of the surveillance activities on SARS-CoV-2 variants established in Lazio Region (Central Italy) and analyzed at the National Institute for Infectious Diseases “L. Spallanzani” in Rome. Results: The majority (92.6%) of the post-vaccine infections showed pauci/asymptomatic or mild clinical course, with symptoms and hospitalization rate significantly less frequent in patients infected after full vaccination course as compared to patients who received a single dose vaccine. Although differences were not statistically significant, viral loads and isolation rates were lower in NPS from patients infected after receiving two vaccine doses as compared to patients with one dose. Most cases (84%) had nAb in serum at the time of infection diagnosis, which in a sub-group of vaccinees, were found similarly able to neutralize Alpha and Gamma variants. Asymptomatic individuals showed higher nAb titres as compared to symptomatic cases (median titre: 1:120 vs 1:40, respectively). Finally, the proportion of post-vaccine infections attributed either to Alpha and Gamma variants was similar to the proportion observed in the contemporary unvaccinated population in Lazio region, and mutational analysis did not reveal enrichment of a defined set of Spike protein substitutions depending on the vaccination status. Conclusion: Our study conducted using real-life data, emphasized the importance of monitoring vaccine breakthrough infections, through the characterization of virological, immunological and clinical features associated with these events, in order to tune prevention measures in the next phase of the COVID-19 pandemic.